Maximum wave-power absorption under motion constraints associated with both controlled and uncontrolled degrees of freedom - Cotten, A.; Forehand, D.I.M. (Applied ocean research, 2020)
A semi-analytical method is derived, which enables optimisation of the power absorption of a collection of wave-interacting bodies, subject to a weighted global motion constraint associated with both the controlled and uncontrolled modes of motion. As an illustrative example, the method is then applied to a six degree of freedom solo duck with various modes of motion under direct control. This is in order to highlight the benefits of employing the extended constraint and to explore the dependence of the existence of a solution on the physical properties of the system. The method is also used to investigate the effects of conceding control of certain degrees of freedom on the capture width ratio of the solo duck.